Quaternary Geology, Aridity and Desertification in Rajasthan - Sinha, Subrata (Annals of Arid Zone, 2016)
The paper highlights the importance of Quaternary Geological studies and the methodology, employed by the Geological Survey to India, to decipher the history and environment of the quaternary era in Rajasthan. It brings out the sequence of events from the earliest humid cold phase, followed by the first generation of more extensive aridity which was separated from the current arid phase by a warm sub-unit phase. After describing these phases, the paper brings out the various geological and geomorphological characteristics obtaining in Rajasthan area that have actively contributed to its arid conditions, besides the role of anthropocentric activities in intensifying the process of desertification in and outside the arid zone.